Simulation of a stand-alone renewable hydrogen system for residential supply (2014)
Computer simulation is a first logical step before taking a project to physical construction beside it is a powerful tool in energy network design. Combined systems are used to improve availability for energy supplied by renewable systems. The main inconvenient of some renewable energy sources is their highly seasonal nature, with great variations over time that can impede their use as the basis for consumption and limits them to peak demand times. The aim of this work is to simulate to verify the energetic sufficiency of a family house with renewable energies (wind, solar-photovoltaic) using a hybrid system of batteries and hydrogen. For that, Simulink®-Matlab® program was used considering meteorological data provided by CINAM (Galician Center for Environmental Research and Information). The model can be applied to determine the feasibility of implementing an energy network in specific places, and to predict energy flows and system behavior throughout the year.